The Japanese Empire and Latin America - Iacobelli, Pedro; Xu Lu, Sidney (University of Hawaii Press, 2023)
The Japanese Empire and Latin America provides a comprehensive analysis of the complicated relationship between Japanese migration and capital exportation to Latin America and the rise and fall of the empire in the Asia-Pacific region. It explains how Japan's presence influenced the cultures and societies of Latin American countries and also explores the role of Latin America in the evolution of Japanese expansion. Together, this collection of essays presents a new narrative of the Japanese experience in Latin America by excavating trans-Pacific perspectives that shed new light on the global significance of Japan's colonialism and expansionism.The chapters cover a variety of topics, such as economic expansion, migration management, cross-border community making, the surge of pro-Japan propaganda in the Americas, the circulation of knowledge, and the representation of the "other" in Japanese and Latin American fictions. By focusing on both government action and individual experiences, the viewpoints examined create a complete analysis, including the roles the empire played in the process of settler identity formation in Latin America. While the colonialist and expansionist discourses in Japan set a stage for the beginning of Japanese migration to Latin America, it was the vibrant circulation of information between East Asia and the Americas that allowed the empire to stay at the center of the cultural life of communities on the other side of the globe. The empire left an enduring mark on Latin America that is hard to ignore. This volume explores long-neglected aspects of the Japanese global expansion; and thus, moves our understanding of the empire's significance beyond Asia and rethinks its legacy in global history
Keywords: HISTORY / Asia / Japan; Japanese -- Latin America -- History; Migrationspolitik; Japan; Lateinamerika